POTENSI TUMBUHAN PIONIR UNTUK WOOD PELLET SEBAGAI BIOENERGI TERBARUKAN - Nurfitri Kartikasari; Chairul Chairul (EnviroScienteae, 2022)
The increasing demand for energy in Indonesia is due to the need or the number of Indonesian population which has increased and is inversely proportional to the availability and production of existing energy. One of the best solutions that can be done is to promote the use of pioneer wood (fast growing plant) as an energy source by processing wood into wood pellets. The method used is a survey method by looking for a place to grow several types of pioneer plants. The purpose of this study was to determine the quality of wood pellets and the potential of several types of pioneer plants tested as environmentally friendly, sustainable renewable bioenergy. The pioneers tested were Acacia mangium, Jatropha curcas, Macaranga tanarius, Swietenia mahagoni, Leucaena leucocephala, and Sesbania grandiflora. The quality of Wood Pellets from pioneer plants is seen from the density ranging from 0.433 gr / cm3 to 0.503 gr / cm3, moisture content of 5.55% - 12.4%, ash content of 1.95-6.2%, and the calorific value of powder from 3657.67% - 4178.18%. Of the several types of pioneer plants tested, the most potential was Leucaena leucocephala because it had met SNI 8021 - 2014 and had the highest calorific value as required.